IT outsourcing in India - Dossani, Rafiq (Henry Stewart Talks, 2011)
India's skills, Entrepreneurship in outsourcing, Enabling policies and regulations, Skills development through engineering education, Skills development through 'on the job' training, Innovation in call centers, Case study of semiconductor design Outsourcing to India, Firm size and outsourcing, Future prospects of outsourcing to India